HEALTHCARE MANAGEMENT TOOLS: AN ASSESSMENT OF THE IMPLEMENTATION OF THE NATIONAL PHARMACEUTICAL CARE MANAGEMENT SYSTEM IN THE STATE OF ALAGOAS - Correia dos Santos, Alexandre (Health and Society, 2024)
Pharmaceutical Assistance has evolved over time and requires a reorganization of management practices. Considering professional experience and working in this area in the State, it was found that the Pharmaceutical Assistance that has been developed in Alagoas has presented some difficulties. Considering that a National Pharmaceutical Assistance Management System was adopted at national level as a management tool, the question arises: “What are the main difficulties encountered in the effective implementation and use of the National Pharmaceutical Assistance Management System as a management tool? control of financial resources invested in the medication acquisition and distribution processes? ” To answer the initial question, the following objective was defined: to evaluate the impacts of the implementation of the National Pharmaceutical Assistance Management System in the State of Alagoas as a Management Tool. In order to achieve the goal, it was decided to develop qualitative and quantitative research as a methodology. Taking into account the results obtained after the research carried out with 90 pharmaceutical professionals working in the health districts of the State of Alagoas, it was possible to verify that the implementation of the HÓRUS system in the State has contributed to the adequate management of the pharmaceutical system, especially in which refers to a better distribution of financial resources for the acquisition of medicines, serving a greater number of people. However, some problems for the adequate implementation of the system were pointed out by the pharmaceutical professionals interviewed, among these, the fact that the system does not have a tab with manual or instructions – to resolve situations that occur routinely – and a shortage of human resources.